Agricultural extension in Africa: vol. 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Volume I contains the keynote and thematic papers, working group reports and seminar recommendations. Topics covered include: the changing role of agricultural extension, research and training; financing information systems; and networking.